1973
DOI: 10.1104/pp.52.5.427
|View full text |Cite
|
Sign up to set email alerts
|

13C/12C Ratio Changes in Crassulacean Acid Metabolism Plants

Abstract: (4,13).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
58
0

Year Published

1975
1975
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(58 citation statements)
references
References 13 publications
0
58
0
Order By: Relevance
“…Laboratory studies have shown the carbon isotope ratio of a single species of CAM plant undergoes an actual shift in value in response to controlled growth conditions (1,3,9,12,15). Field studies with succulent plants suspected of being CAM have shown a relationship between environmental conditions and carbon isotope ratio (10,11,14,16 Titratable Acidity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory studies have shown the carbon isotope ratio of a single species of CAM plant undergoes an actual shift in value in response to controlled growth conditions (1,3,9,12,15). Field studies with succulent plants suspected of being CAM have shown a relationship between environmental conditions and carbon isotope ratio (10,11,14,16 Titratable Acidity.…”
mentioning
confidence: 99%
“…The photosynthetic metabolism can be shifted from CAM to C3 metabolism (1,3), with a mean shift in the total tissue o-t3C value ranging from 3 to 4 0/oo (our calculation from original data). Additionally, the photosynthetic metabolism can be shifted from C3 to CAM metabolism (9, 15) with a mean shift in the total tissue o-13C value ranging from 6 to 8 0/oo (our calculation from original data).…”
mentioning
confidence: 99%
“…Bender et al (2) have suggested the "C/'lC ratios of Crassulaccan acid metabolism plants are indicative of CO3 fixation by RuDP or PEP carboxylase. Lerman et al (11) have advanced the idea that the wide range of 8 DBC values is due to the contribution of C3 and C4 pathways in Crassulaccan acid metabolism plants.…”
mentioning
confidence: 99%
“…The C 4 pathway in grasses is favored by warmer temperatures (Ehleringer et al 1997;Long 1999;Teeri and Stowe 1976), while C 4 dicotyledonous taxa are associated with increased aridity (Ehleringer et al 1997;Long 1999;Stowe and Teeri 1978). The final pathway, termed CAM (crassulacean acid metabolism), is used by most succulents (Bender et al 1973;Ranson and Thomas 1960). CAM plants can mimic either C 3 or C 4 stable carbon isotopic signatures and have ranges from around -33 to -14 mill (Bender et al 1973;Griffiths 1992).…”
Section: Shifts In Vegetation Structure Suggested By Changes In Soil mentioning
confidence: 99%
“…The final pathway, termed CAM (crassulacean acid metabolism), is used by most succulents (Bender et al 1973;Ranson and Thomas 1960). CAM plants can mimic either C 3 or C 4 stable carbon isotopic signatures and have ranges from around -33 to -14 mill (Bender et al 1973;Griffiths 1992). However, in Central and South Texas, CAM plants seem to produce isotopic signatures that are comparable to the lower range of C 4 plants (see Boutton et al 1998: 18;.…”
Section: Shifts In Vegetation Structure Suggested By Changes In Soil mentioning
confidence: 99%